Integrasi Digital Service Innovation dalam Kebijakan Dividen: Analisis Mediasi Ukuran terhadap Nilai Perusahaan Tobin's Q - Hasti Pramesti Kusnara; Herry Achmad Buchory Buchory; Rizky Ferari Oktavian Oktavian; Siti Wulansari Wulansari; Ignatius Oki Dewa Brata (Jurnal Dimamu, 2026)
This study investigates the integration of Digital Service Innovation in dividend policy and its impact on firm value, measured by Tobin's Q, with firm size as a mediating variable. Employing Signaling Theory and Agency Theory as the theoretical underpinnings, this research addresses the "Dividend Puzzle" within the context of the digital economy, where investors consider not only payout ratios but also a firm's capacity for digital innovation. Using a sample of 45 digital-sector and banking companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2025, the study employs Structural Equation Modeling with Partial Least Squares (SEM-PLS/SmartPLS) to simultaneously test mediation and moderation effects. The operationalization of variables includes the Dividend Payout Ratio (DPR) for dividend policy, the natural logarithm of total assets for firm size, and a digital innovation index derived from annual report disclosures. Results indicate that: (1) dividend policy exerts a significant positive effect on firm value; (2) firm size partially mediates the dividend-firm value relationship; and (3) Digital Service Innovation significantly moderates and strengthens the positive effect of dividend policy on Tobin's Q. These findings contribute empirical evidence to classical financial theory (M-M Theory and Bird-in-the-Hand Theory) by incorporating a technological dimension, and provide practical guidance for digital business managers in aligning dividend policies with digital innovation strategies.